2023
DOI: 10.3390/cells12071026
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Novel Canine Osteosarcoma Cell Lines from Chemotherapy-Naïve Patients

Abstract: The present study aimed to establish novel canine osteosarcoma cell lines (COS3600, COS3600B, COS4074) and characterize the recently described COS4288 cells. The established D-17 cell line served as a reference. Analyzed cell lines differed notably in their biological characteristics. Calculated doubling times were between 22 h for COS3600B and 426 h for COS4074 cells. COS3600B and COS4288 cells produced visible colonies after anchorage-independent growth in soft agar. COS4288 cells were identified as cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…One well-studied long non-coding RNA, MALAT1, plays a crucial role in the regulation of multiple signaling pathways in osteosarcoma cells, involving tumor proliferation and metastasis, resulting in a low proliferation capacity. Notably, MALAT1 is highly expressed in two canine osteosarcoma cell lines, COS3600 and COS4074 [46]. Several studies have confirmed that MALAT1 plays a crucial role in the regulation of multiple signaling pathways in osteosarcoma cells, involving tumor proliferation and metastasis via sponging miRNAs [47][48][49].…”
Section: The Molecular Function and Clinical Use Of Lncrna In Other C...mentioning
confidence: 98%
“…One well-studied long non-coding RNA, MALAT1, plays a crucial role in the regulation of multiple signaling pathways in osteosarcoma cells, involving tumor proliferation and metastasis, resulting in a low proliferation capacity. Notably, MALAT1 is highly expressed in two canine osteosarcoma cell lines, COS3600 and COS4074 [46]. Several studies have confirmed that MALAT1 plays a crucial role in the regulation of multiple signaling pathways in osteosarcoma cells, involving tumor proliferation and metastasis via sponging miRNAs [47][48][49].…”
Section: The Molecular Function and Clinical Use Of Lncrna In Other C...mentioning
confidence: 98%